2018
DOI: 10.21608/edj.2018.78060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of material on stress transmission to the supporting structures in Kennedy Class I restored by Telescopic-retained Removable Partial Denture. (Strain Gauge Study)

Abstract: Objectives:The aim of this in-vitro study was to compare the stresses transmitted to the abutments in mandibular Kennedy class I restored with telescopic-retained removable partial denture (RPD) made from two different materials; PolyEther Ether Ketone (PEEK) and Co-Cr alloy. Materials and Methods:One mandibular model representing Kennedy class I, with second premolars as the last standing abutments, was fabricated using epoxy resin. Poly Vinyl Siloxane (PVS) impression material was used to simulate the mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In a previous study by Emera, et al that was concerned with evaluation and comparison of stresses applied to the implants retaining mandibular complete overdenture with telescopic attachments made of Zirconia and PEEK they explained the higher stress values recorded by all PEEK group by the less flexure strength of PEEK (150-330 MPa) in comparison to ZrO2 (630-970 MPa) (27). Also, the tensile stresses to the ridge were coincident with a previous study by Bahgat, et al, (14) that was concerned with one treatment modality used for rehabilitation of mandibular Kennedy Class I cases, using two different materials, Co-Cr alloy and PEEK, and their effect on the strain induced in the supporting structures for these telescopic-retained (RPDs). The findings proved that PEEK telescopic retained RPDs resulted in statistically significant higher tensile strains in most of the channels when compared to Co-Cr RPD.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In a previous study by Emera, et al that was concerned with evaluation and comparison of stresses applied to the implants retaining mandibular complete overdenture with telescopic attachments made of Zirconia and PEEK they explained the higher stress values recorded by all PEEK group by the less flexure strength of PEEK (150-330 MPa) in comparison to ZrO2 (630-970 MPa) (27). Also, the tensile stresses to the ridge were coincident with a previous study by Bahgat, et al, (14) that was concerned with one treatment modality used for rehabilitation of mandibular Kennedy Class I cases, using two different materials, Co-Cr alloy and PEEK, and their effect on the strain induced in the supporting structures for these telescopic-retained (RPDs). The findings proved that PEEK telescopic retained RPDs resulted in statistically significant higher tensile strains in most of the channels when compared to Co-Cr RPD.…”
Section: Discussionsupporting
confidence: 83%
“…They explained this result by the much higher Young's modulus of Co-Cr alloy (220-230 GPa) (28). Compared to that of the PEEK (3-4 GPa) (26) and concluded that Co-Cr alloy telescopic-retained RPD could still be considered a better choice for rehabilitation of the Kennedy Class I partial edentulous situations compared to PEEK one, where Co-Cr generated less and better pattern of stresses to the denture-supporting structures (the residual alveolar ridges and abutments) (14). Rigid major connectors resist deflection, deformation, and torquing forces that could be conducted to the supporting structures as destructive forces (29).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Because of the tiny size and linearity of the resistance rate change, this method of stress analysis has provided a better understanding of stress transmission and distribution in different prosthetic appliances and different types of attachments in RPDs. 2,26,27 To the authors' knowledge, there is no available literature to evaluate the strains developed by zirconia and metal RBAs. Hence, the aim of this study was to assess the strains transferred by zirconia and metal RBAs to the maxillary distal extension RPD supporting structures and compare them with the strains generated by the extracoronal attachment with full veneer retainers.…”
Section: Introductionmentioning
confidence: 99%